UTILIZING TEACHING METHODS AND REFLECTING ON STUDENTS’ PERSONAL TRAITS IN LEARNING BELAJAR DAN PEMBELAJARAN SUBJECT - Marpaung, Tiarma Intan; Sinurat, Bloner; Sitinjak, Gloria (Dharmas Education Journal (DE_Journal), 2024)
The objectives of this study are to investigate whether (1) Problem- Based Learning and Jigsaw teaching methods significantly affect students’ learning; (2) personal traits significantly affect the students’ learning; (3) there is an interaction between teaching methods and personal traits on the students’ learning. This study was conducted by using experimental research with factorial design 2 x 2. The sample of the study were students of Belajar dan Pembelajaran Subject in Teacher Training Faculty of Universitas HKBP Nommensen Pematangsiantar group FK- 7 and FK- 11 academic year 2023/2024. These two classes are chosen as the sample purposively since the researcher teaches the subject for those groups only. The instruments used for data collection were essay test and questionnaire. The data were analyzed by using two- way ANOVA. The research finding showed that (1) problem- based learning and jigsaw significantly affect the students’ achievement in Belajar dan Pembelajaran Subject (sig. value = 0.013 < 0.05 at α = 0.05); (2) personal traits significantly affect students’ achievement in Belajar dan Pembelajaran subject (sig. value = 0.037 < 0.05 at α = 0.05); (3) there is an interaction between teaching methods and personal traits on the students achievement in Belajar dan Pembelajaran Subject (sig. value = 0.000 < 0.05 at α = 0.05). Thus, teaching methods and personal traits significantly affect the students’ achievement in Belajar dan Pembelajaran Subject